ANALISIS DAMPAK SISTEM PENGELOLAAN SAMPAH TPA TERJUN DI KOTA MEDAN - Adilla Hafizah; Diah Ayu Pratiwi, Diva Nada Rizky Nuzlan; Abdurrozzaq Hasibuan (CV. ADIBA AISHA AMIRA, 2023)
Garbage is a problem that needs attention because it can have a negative impact on the environment and human health. The city of Medan, including North Sumatra, has problems with waste management that are not yet optimal. One of them is the Final Disposal Site (TPA) in Medan City, namely TPA Niagara. Therefore, this research was conducted to determine the impact of the waste management system at the TPA Niagara City of Medan. The method used by researchers is a descriptive-qualitative approach. Primary data was obtained through observation and interviews with 4 informants, including TPA Plunge officers and the surrounding community. The research was conducted from March to May 2023. The results of this study found that TPA Niaga uses the open dumping method in waste management. This method causes environmental pollution, including soil, groundwater, and air. This pollution can disrupt ecosystems and threaten human health. In waste management, TPA Niaga also cooperates with the Pangkalan Susu PLTU to use organic waste as an alternative fuel